Teleducation about Cleft Lip and Palate: An Interdisciplinary Approach in the Promotion of Health - Corrêa, Camila de Castro; Freire, Thais; Zabeu, Júlia Speranza; Martins, Aline; Ferreira, Rafael; Francisconi, Paulo Afonso Silveira; Dutka, Jeniffer de Cássia Rillo; Blasca, Wanderléia Quinhoeiro (International Archives of Otorhinolaryngology, 2015)
Introduction The Young Doctor Project (YDP) uses Telehealth and Interactive Teleducation instruments to promote the integration of different areas of health and to build knowledge. This methodology can also foster public awareness on various issues related to health. In this context, the objective of this study was to emphasize cleft lip and palate (CLP), which is one of the most common birth defects in Brazil.Objective The study aimed to apply a model of education regarding CLP, based on the dynamics of the YDP, and to evaluate the participants' knowledge acquired after participating in the YDP.Methods The participants were 41 students, 13 to 15 years of age and at the eight- and ninth-grade levels in a private elementary school in Bauru (Brazil). To analyze the performance of the participants, a questionnaire was administered before and after the completion of the training program. The training program was structured in three steps using: (1) interactive teleducation classes, (2) a cybertutor, and (3) practical activities.Results There was a statistically significant difference between the pre- and postparticipation questionnaire results. The improved performance of participants is evidenced by the increase in the rate of correct answers on all issues.Conclusion The YDP on CLP was applied in the school setting following the three steps recommended by the project, and, after the implementation of the training program, there was a significant increase in participants' knowledge of CLP. The YDP on CLP proved an effective tool in promoting health education.
Keywords: cleft palate; speech, language, and hearing sciences; dentistry; health education; telehealth